Using games in accounting and finance classes - Azis, Saflina; Mat, Mustafa Kamal (Universiti Teknologi MARA, 2009)
For most students, Accounting and Finance seem to be serious and tough courses which involve a lot of calculations. In normal condition, students tend to ignore the theoretical parts of the subjects and pay more attention to the calculation items. This is because students do not enjoy reading and prefer working on the more practical part of the courses. Thus, the authors attempt to enhance students' level of reading and interest on the theoretical parts of the courses by introducing games during the teaching and learning process. The objective of the paper is to examine the perception of the students towards the use of games as part of the learning process for the theoretical parts of these courses. Students reported that the use of the games stimulate the level of thinking and encourage the habit of reading in these courses.